The Effect of the Characteristics of the Drama based on the Webtoon on the Attitude and Behavior of the Viewer - Lee, Sin-Bok (International Journal of Membrane Science and Technology, 2023)
Recently, dramas based on webtoons are gaining popularity. The reason is that dramas which are based on webtoons is not only highly recognized but also have a strong story, so there is a high probability that they can succeed as a masterpiece drama. In this study, based on previous studies on the characteristics of the dramas which are based on webtoons, we tried to investigate how the attitude of drama viewers and the behavior of drama viewers can change, by confirming the characteristics of the dramas based on the webtoons. For our study, we distributed and collected 252 questionnaires filled out from September 1 to September 14, 2022 to adult men and women in their 20s and 30s. The results of this study are summarized as follows. First, among the characteristics of the dramas which were based on webtoons, the reputation of the original work, or webtoons, had a positive effect on the satisfaction of drama viewers, but it had no effect on flow of the drama viewers. Second, among the characteristics of the drama in which the webtoon is the original work, the suitability of original work and drama imaqge and the suitability of actor casting were found to have a positive effect on both satisfaction and flow of drama users.Third, among the characteristics of the dramas which were based on webtoons, it was found that the platform characteristics had no effect on both satisfaction and flow of drama viewers. Finally, it was found that the satisfaction and flow of drama viewers had a positive effect on all behaviors of the drama viewers.